Forecasting Inputs Demands on the Quality of Animal Breeding Public Services in Uganda: A Supply Chain Perspective - Lagu, Charles; Kugonza, Sylvester; Nagitta, Oluka Pross; Andama, Morgan (Journal of Agriculture Food and Development, 2020)
The study focused on supply chain forecasts for inputs on the quality of animal breeding public services in selected cattle corridor districts (Mbarara, Mubende, Luwero and Soroti) of Uganda. The key question was, what effect key breeding inputs (liquid nitrogen and frozen semen) had on quality of animal breeding services. The research adopted cross-sectional survey design embracing quantitative approaches. Data was captured using review of records from the Genetic Centre, Artificial Insemination (AI) technicians, and Field Extension workers. The work included forecasting and trend analysis for liquid nitrogen and frozen semen production and costs for the period 2019-2023 at the current level of inputs and manpower at the National Animal Genetic Resources Centre and Data Bank. The study established that 77.3% of the produced liquid nitrogen will be utilized by the year 2023. In the same vein, 62.6% of the frozen semen produced will be utilized by the year 2023. The study predicted the costs related to production, maintenance and repairs for liquid nitrogen plants and projected semen production, maintenance of the bulls, and veterinary costs. Other forecasted costs were for semen importation per annum for breeds and genetic diversity in the country. The study guides NAGRC&DB and other players in the animal resources value chain to undertake forecasts and trend analysis for better planning, budgeting, strategy and delivery of quality animal breeding services in selected cattle corridor districts of Uganda. The topic of operational efficiencies for the circulation and usage of key breeding inputs dependent on farming system and agro-ecology should be explored in Uganda.
Keywords: Breeding Inputs; Frozen Semen; Genetic Centre; Liquid Nitrogen; Trends Analysis